1999
DOI: 10.1093/carcin/20.11.2075
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glycine prevents the development of liver tumors caused by the peroxisome proliferator WY-14,643

Abstract: Previous studies demonstrated that dietary glycine prevents elevated rates of cell proliferation following treatment with the peroxisome proliferator and liver carcinogen WY-14,643. Since increased cell replication is associated with the development of hepatic cancer caused by peroxisome proliferators, glycine may have anti-cancer properties. Therefore, experiments were designed to test the hypothesis that dietary glycine would inhibit the hepatocarcinogenic effect of WY-14,643. Male F344 rats were fed four di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 29 publications
0
36
1
1
Order By: Relevance
“…But the data overall indicate that Kupffer cells likely do not contribute to the tumor promoting activities of PCB-77 and PCB-153. These results clearly differ from those of Rose et al (1999a), who found that Kupffer cell inactivation by dietary glycine inhibited liver carcinogenesis by the peroxisome proliferator Wy-14,643. The findings of the present study imply that Kupffer cell activation may not be essential for hepatic tumor promotion.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…But the data overall indicate that Kupffer cells likely do not contribute to the tumor promoting activities of PCB-77 and PCB-153. These results clearly differ from those of Rose et al (1999a), who found that Kupffer cell inactivation by dietary glycine inhibited liver carcinogenesis by the peroxisome proliferator Wy-14,643. The findings of the present study imply that Kupffer cell activation may not be essential for hepatic tumor promotion.…”
Section: Discussioncontrasting
confidence: 99%
“…For this, we examined the ability of dietary glycine to inhibit PCB-induced tumor promotion, since several studies have shown that glycine decreases the production of superoxide and TNF-α by Kupffer cells (Ikejima et al 1996;Rose et al 1999a;Rose et al 1997a;Rusyn et al 1999). The inhibition by glycine of TNF-α production by Kupffer cells is not as strong as using agents such as gadolinium chloride or methyl palmitate, but that may be an advantage for a therapeutic agent (Rentsch et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Previous studies have shown that dietary glycine inhibits the growth of B16 melanoma tumors in mice 15 and certain carcinogen induced liver tumors. 16 In these studies glycine inhibited growth of an established tumor in vivo but did not have any cytotoxic effect on tumor cells in vitro. Thus, Rose postulated that glycine's primary effect would be on host tissue but convincing evidence for this hypothesis was not provided.…”
Section: Introductionmentioning
confidence: 84%
“…In direct contradiction, however, glycine has been shown to prevent tumorigenesis [122] and it is a potent anti-angiogenic nutrient that suppresses tumour growth, possibly through activation of a glycine-gated chloride channel [123]. Impaired glycine synthesis likely has other adverse effects as well, such as the possibility that glyphosate interferes with glycine conjugation of benzenebased compounds.…”
Section: Impaired Glycine Synthesismentioning
confidence: 99%